Characterization of microsatellite markers in the African tropical tree species Guibourtia ehie (Fabaceae, Detarioideae)1. (26th July 2017) - Tosso, Félicien; Doucet, Jean‐Louis; Migliore, Jérémy; Daïnou, Kasso; Kaymak, Esra; Kameni, Franck S. Monthe; Hardy, Olivier J.
Abstract : Premise of the study: Microsatellite primers (simple sequence repeats [SSRs]) were developed in Guibourtia ehie (Fabaceae, Detarioideae) to study population genetic structure and the history of African vegetation. Methods and Results: We isolated 18 polymorphic SSRs from a nonenriched genomic library. This set of primer pairs was tested on four populations, and the results showed two to 16 alleles per locus with mean observed and expected heterozygosities of 0.27 ± 0.05 and 0.57 ± 0.05, respectively. Cross‐amplification tests in 13 congeneric species were successful for the four taxa belonging to the subgenus Gorskia . Conclusions: This set of microsatellite markers will be useful to investigate the phylogeography and population genetics of G. ehie, a key representative of African semideciduous moist forests.